James Stewart : Universal Hollywood icons collection [videorecording (DVD)]. - Stewart, James, 1908-1997; Hull, Josephine, 1877-1957; Drake, Charles, 1917-1994; Kellaway, Cecil, 1891-1973; Winters, Shelley; Duryea, Dan, 1907-1968; McNally, Stephen, 1913-1994; Allyson, June, 1917-2006; Morgan, Harry, 1915-2011; Langford, Frances; Armstrong, Louis, 1901-1971; Krupa, Gene, 1909-1973; et al. (Universal Pictures Home Entertainment, 2016)
Harvey: Comedy about a good-natured fellow whose constant companion is a six-foot tall invisible rabbit. His sister is determined to marry her daughter off and decides to commit her brother to a mental hospital to get him out of the way. Due to a mix-up the sister is committed instead, and it is up to the kindly brother and his imaginary friend to straighten things out!